Berlioz - Rushton, Julian (Cambridge New York Cambridge University Press, 2023)
"Berlioz's Symphonie fantastique attracts wide audiences and is acknowledged as a landmark of music history. This book situates the symphony within French Romanticism and considers influences, literary as well as musical, that shaped its conception. Richly detailed and accessibly written, it will appeal to music lovers, scholars, and students"--
Introduction, Programme, Outline -- Literary and Musical Romanticism -- Symphonie fantastique in Berlioz's lifetime -- First movement: 'Rêveries, passions' -- Second movement: 'Un bal' -- Third movement: 'Scène aux champs' -- Fourth movement: 'Marche au supplice' -- Fifth movement: 'Songe d'une nuit de Sabbat' -- The Sequel; Reception by Composers -- Reception: Schumann and Musical Form -- Other Approaches; Conclusion
Includes bibliographical references and index.
Keywords: Berlioz, Hector -- 1803-1869; Symphony; Program music; Musical analysis; Music history